Safety analysis of China's marine energy channel based on Multi - Agent simulation. (February 2019) - Shen, Yang; Guo, Yongchen; Chen, Wenlin
Abstract: According to the actual situation of China's oil imports and transportation, the Middle East route was selected as the research object. Based on Multi-Agent modeling and simulation method, this paper is going to start at the micro level to simulate the energy transport process. Select oil carrier, pirate and hurricane as the agents after analyzing the security factors influencing China's marine energy channel; build a multi-agent model of China's marine energy channel (Middle East route) with agents' attributes and interaction rules; design and conduct simulation program on NetLogo platform. Three experimental schemes are designed to verify the model validity and study the inherent and actual safety factors' impact on China's marine oil imports. The result shows the simulation model is validity; the quantity of China's VLCC is far from carring all the oil transportation on the Middle East route; the increase in the number of tankers is usually lower than that in the total amount of oil imports, while the raise of pirates and hurricanes will cause a greater reduction on oil imports.